Pengaruh Lingkungan Kerja, Pengalaman Kerja melalui Pelatihan Kerja Terhadap Kinerja Karyawan JNT Kabupaten Batanghari - Raden Hebat Kurnia; Muhammad Oceano Fauzan (Universitas Batanghari, 2022)
In this study, the variables used were the work environment, work experience, job training, performance of the employees of the Batanghari Regency JnT Office. The purpose of this study is to provide input to the Batanghari Regency JnT Office and add knowledge to readers. The research method used is by distributing questionnaires to the employees of the JnT Office in Batanghari Regency, in answering the questionnaire respondents simply mark the column that has a Likert's Scale (1 - 5) above it. The results obtained from this study, partially the work environment on training has a positive and significant effect, while work experience has a negative and insignificant effect on job training. The work environment variable has a positive and significant effect on performance, but the work experience variable has a negative and insignificant effect on the performance of the Batanghari Regency JnT Office employees. The job training variable has a positive and significant influence on the performance of the employees of the JnT Office in Batanghari Regency. Meanwhile, simultaneously, the work environment, work experience through job training has an effect and is significant.